PERAN ADIPURA PADA PELAKSANAAN SISTEM PENGELOLAAN SAMPAH DI INDONESIA - Sidik, Muhamad Ansorudin (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
Solid waste management is a system involving all subsystems of management such asÃ‚Â institutional, law, financing, operational, and community participation. Waste law whichÃ‚Â shelters the solid waste management is the umbrella of all local regulation (Perda).Ã‚Â But in fact, its implementation and aplication have not run well as expected. Using aÃ‚Â simple analisys method from personal experience as an Adipura award appraiser, thewriter tried to reveal the strengths and weaknesses in waste management all this time.Ã‚Â The result shows that local governments, in general, havenÃ¢â‚¬â„¢t considered the wastemanagement subsystems integratedly in handling the municipal garbage. They usuallyÃ‚Â see the problem partially, not as an integrated system which includes all the subsystems.Ã‚Â Municipal waste management should not become a proses which is independent fromthe other subsystems. It is recommended that the head of regional government seeÃ‚Â the waste management.